Factors associated with dental fluorosis in school children in southern Brazil: a cross-sectional study - Marina Sousa Azevedo; Marília Leão Goettems; Dione Dias Torriani; Flávio Fernando Demarco (Sociedade Brasileira de Pesquisa Odontológica, 2014)
This cross-sectional study assessed risk factors for dental fluorosis (DF) among 8- to 12-year-old children in southern Brazil. Children attending 20 schools were randomly selected (n = 1,196). They were interviewed and their parents answered a questionnaire that was sent home. Prevalence of DF was 8.53% (modified Dean's criteria), and the prevalence of severe DF was 0.17%. The results of multiple logistic regression analyses indicated that DF was associated with a higher frequency of tooth brushing and with initial use of fluoride toothpaste at the emergence of the first tooth. DF does not constitute a public health problem in southern Brazil.